(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article delves into the sociolinguistic aspects of terminology, exploring how language reflects societal norms, values, and power structures. It examines the dynamics of terminology formation, usage, and interpretation within various social contexts. Drawing on sociolinguistic theories and research methodologies, this study investigates the multifaceted nature of terminology and its implications for communication and social identity.